2012
DOI: 10.3892/ijmm.2012.1151
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of PTEN in hepatic tissue and hepatic stellate cells during rat liver fibrosis and its reversal

Abstract: To evaluate the change in phosphatase and tensin homology deleted on chromosome ten (PTEN) expression in liver fibrogenesis, particularly the reversal of fibrogenic liver tissues, and to investigate the relation with the proliferation and apoptosis of hepatic stellate cells (HSCs) in vivo, a rat model of hepatic fibrosis was established by hypodermic injection of carbon tetrachloride (CCl4) mixed with olive oil at the concentration of 40% for 5 weeks (2 ml/kg, twice a week). Reversal of fibrosis was achieved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Decreased PTEN expression has been reported in fibrotic diseases of the lungs, heart, skin as well as liver [1418]. Specifically, deletion of the Pten gene in mice results in excess deposition of type I collagen, while PTEN overexpression can reverse chemical-induced liver fibrosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased PTEN expression has been reported in fibrotic diseases of the lungs, heart, skin as well as liver [1418]. Specifically, deletion of the Pten gene in mice results in excess deposition of type I collagen, while PTEN overexpression can reverse chemical-induced liver fibrosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the expression of PTEN was decreased in rat fibrotic liver tissues and HSCs induced by bile duct ligation in vivo [ 12 ]. During the reversal of liver fibrosis, pretreated PTEN mRNA and protein expression normalized, showing the relationship between PTEN and the severity of rat hepatic fibrosis[ 13 ]. The study presented herein investigated the in vitro and in vivo effects of PTEN on liver fibrosis using adenoviral transduction of wild-type PTEN (Ad-PTEN), mutant PTEN (Ad-G129E), and PTEN short hairpin RNA (PTEN shRNA) to better characterize the molecular mechanisms of PTEN in liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…As a chemical hepatotoxicant, CCL4 has been widely used for its reliability to induce liver fibrosis and cirrhosis in experiments [10,11], despite its high mortality rate (43.3%). This study demonstrates that CCL4 can also be used to induce hypersplenism.…”
Section: Discussionmentioning
confidence: 99%